UPAYA MENINGKATKAN BACA QUR’AN SISWA KELAS IV MELALUI METODE TILAWATI DI SDN CIJAYANTI 02 - Bayu Rizki Amali; Zahid Mubarok; Retno Triwoelandari (Universitas Pahlawan Tuanku Tambusai, 2022)
This research is motivated by several problems that occur in the learning activities of SD Negeri Cijayanti02, so that the activities and learning outcomes obtained by students have not reached the KKM that has been set. Based on observations, it is known that the passive activity of students in following the learning process and the lack of variety of teachers in using methods affect the low learning outcomes and learning activities of students. The purpose of this study is to find out the increase in activity and learning outcomes of fourth grade students at SD Negeri Cijayanti 02 in learning the Qur'an using the Tilawati method. This research is included in the Classroom Action Research (CAR) which was carried out in two cycles. Each cycle consists of 2 meetings. One cycle consists of 4 stages of activity, namely the planning stage, the implementation stage, the observation stage and the reflection stage. The subject of this research is class IV SD Negeri Cijayanti 02 with a total of 16 students consisting of 8 male students and 8 female students, in learning Islamic Religious Education in the 2021/2022 academic year using the 2013 curriculum. The data collection techniques used in this study is the analysis of qualitative and quantitative data. By using the Tilawati method students are able to improve learning outcomes and encourage student activity. This can be seen from the results of student tests in the first cycle of 6.00 and the second meeting an average of 6.5 (75.5 %) and cycle II an average of 6.93 (85.71%). Keyword: Read the Qur'an, Tilawati Method